Pengaruh Disiplin, Motivasi, Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan PT.Belantara Subur di Sotek Penajam Paser Utara: Pengaruh Disiplin, Motivasi, Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan PT.Belantara Subur di Sotek Penajam Paser Utara - Titania Aulia; Tamzil Yusuf; Tutik Yuliani; Didik Hadiyatno; Imam Arrywibowo (MEDIA RISET EKONOMI [MR.EKO], 2023)
The purpose of this study was to determine the effect of discipline, motivation and work environment on the work of PT. Fertile Wilderness in North Penajam Paser Sotek. This research was conducted at PT. Subur wilderness in North Penajam Paser Sotek, with 91 respondents, this research method uses quantitative methods. Data collection by way of observation and distribution of direct questionnaires. The data analysis technique used is multiple linear analysis by conducting instrument tests, classical assumption tests, and partial hypothesis testing (t-test). The results showed that the variables of discipline, motivation and work environment had a positive and significant effect on the job satisfaction of employees at PT. Fertile Wilderness in North Penajam Paser Sotek.